THE WIFE’S PARTICIPATION TO INCREASE OF FISHERMEN HOUSEHOLD INCOME IN BEROMBANG VILLAGE PANAI HILIR SUB DISTRICT LABUHANBATU REGENCY OF NORT SUMATERA PROVINCE - Bangun, Kameliana; Nugroho, Firman; ', Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted in the Berombang Village Labuhanbatu North Sumatra province in April 2015. The aim of this study is Knowing wife's participation in increasing the household income of fishermen in the Berombang Village method used is survey method. Determination of the respondents random sampling (simple random sampling). The poopulation Berombang Village has a population of 32 577 respondent. Wife of a fisherman ranged between Rp. 300,000 to Rp. 2,800,000 / month. Husband earned income (fishing) ranged RP. 1,121,205 / month. Average income of household Rp. 2,778,738 / month. By comparison husband and wife income2of Rp. 411 359. T test test results showed revenue wives and husbands are not real perberbedaan, the difference is shown by 0.276> 0.005. While the proportion of the income of fishermen wife on household income is high (51-100%).Keyword: Participation Wife, Income, Household